The Asian Development Model and Mining Reforms in Indonesia - John Passant; John McLaren; Parulian Silaen; Ananda Wickramasinghe (Australasian Accounting, Business and Finance Journal, 2015)
The aim of this paper is to provide accounting, marketing, management, finance and legal professionals who are engaged with emerging economies with an introduction to the ‘Asian Development Model’ and to use the mining reforms in Indonesia as an example of the Model in operation. This will assist those professionals in recognising the challenges faced by businesses in Australia and New Zealand when governments in South East Asian countries attempt to ‘catch up’ to the developed world and at the same time attempt to spread the benefits of the development to their people. The paper argues that there is an Asian Development Model and that the Indonesian mining reforms, in particular the requirement over time for 51 percent Indonesian Government ownership and the ban on the export of unprocessed resources, represent an attempt by the Indonesian State to speed up industrialisation in their country and to spread more of the benefits from mining to ordinary citizens in the recently democratised and politically decentralised country. In attempting to show strength however, the Indonesian state is exposing some weakness. The impact on jobs, revenue and production has been adverse although Foreign Direct Investment has increased. This latter may be because it is foreign multinational mining companies who are better placed than local mining enterprises to build smelters. The success of developing mining might be at the expense of local capital. In other words state intervention does not always produce all of the desired outcomes. It is not a panacea.
Keywords: Asian Development Model; Mining Reforms; Indonesia